Image Based Hand Recognitions - Das, Madhulina; Bandyopadhyay, Samir Kumar (International Journal of Computer Sciences and Engineering, 2014)
The use of hands as biometric evidence is not very new, and commercially available. The proposed method is compared to other methods a method for extension. This will give better result as seen from the output. The personal attributes used in a biometric recognition system may be hand recognition This paper investigates a new approach to achieve performance improvement for hand area geometry systems by recognition of area of finger and hand and also the relative area between finger and hand which reduces the conventional hand geometry based personal verification systems.